Design and control aspects of the reluctance synchronous machine with a cageless flux-barrier rotor - Mackay, Adam T.(Adam Thomas) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1993.